2018
DOI: 10.14715/cmb/2018.64.6.9
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin increases miR-21 to promote migration in HCC

Abstract: Hepatocellular carcinoma (HCC) is a common human malignancy. In this study, we aimed to investigate the serum levels of visfatin and miR-21 in HCC patients, to analysis the relationship between the pathological features and the plasma level of visfatin or miR-21, and to explore the roles of visfatin and miR-21 in migration of HCC cells. Our results showed that the serum levels of visfatin and miR-21 were significant higher in HCC patients than healthy subjects. The diagnostic sensitivity of serum visfatin was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Our data also show a significant increase in the serum levels of visfatin in HCC and HCV patients compared to the NC groups. These data are in concordance with these of Ninomiya et al, (2011) and Liang et al, (2018) who found that visfatin level is significantly higher in HCC patients compared to control group, and that it induces HCC cell migration via upregulation of miR-21. In our study, we found that increased serum level of visfatin associates significantly with increased mortality rates of the patients.…”
Section: Discussionsupporting
confidence: 92%
“…Our data also show a significant increase in the serum levels of visfatin in HCC and HCV patients compared to the NC groups. These data are in concordance with these of Ninomiya et al, (2011) and Liang et al, (2018) who found that visfatin level is significantly higher in HCC patients compared to control group, and that it induces HCC cell migration via upregulation of miR-21. In our study, we found that increased serum level of visfatin associates significantly with increased mortality rates of the patients.…”
Section: Discussionsupporting
confidence: 92%
“…Experimental evidence shows that mi RNAs can be used as oncogenes or tumor suppressor genes in HCC [36]. For example, miR-21 is used as a cancer-promoting factor in HCC, which is highly expressed in HCC and induces cell proliferation, invasion and chemotherapy resistance [37]. In contrast, miR-122, as a tumor suppressor, is lowly expressed in HCC [38].…”
Section: Discussionmentioning
confidence: 99%
“…NAMPT is a pleiotropic protein implicated in the pathogenesis of cancer and obesity and its complications, including insulin resistance, diabetes, and aging (Goktas et al 2013;Shackelford et al 2013;Zhang et al 2017;Zhao et al 2017;Liang et al 2018;Poljsak 2018;Ohanna et al 2018). There are data reporting that inhibition of NAMPT by specific inhibitors decreases cancer growth, induces apoptosis, suppresses cell growth, and enhances the susceptibility to oxidative stress and also sensitizes the glioblastoma cells to temozolomide (Abu Aboud et al 2016;Feng et al 2016;Alaee et al 2017;Xu et al 2017;Tabassum et al 2018).…”
mentioning
confidence: 99%
“…It has also been shown that down-regulation of NAMPT expression by miR-206 reduces survival of the breast cancer cells that NAMPT expression is up-regulated in pediatric gliomas and that its overexpression induces glioma and other cancers growth (Minchenko et al 2015a;Lucena-Cacace et al 2017;Zhao et al 2017;Hesari et al 2018). Moreover, NAMPT can promote hepatocellular carcinoma cell migration through the up-regulation of miR-21 (Liang et al 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation